Averaged Optimization and Finite-Time Thermodynamics - Tsirlin, Anatoly (Entropy (Basel), 2020)
The paper considers typical extremum problems that contain mean values of control variables or some functions of these variables. Relationships between such problems and cyclic modes of dynamical systems are explained and optimality conditions for these modes are found. The paper shows how these problems are linked to the field of finite-time thermodynamics.